(untitled) (Journal of the Association for the Study of Australian Literature, 2009)
This essay argues that understanding the locatedness of poetry is crucial as a measure by which to sift the high rhetorics of national, cosmopolitan, globalising discourses. In an analysis of the poetry of Indigenous writers Tony Birch, Sam Wagan Watson and Lionel Fogarty, and of the Federal Government’s Apology to the Stolen Generations, we can see more clearly the role of literature, and particularly poetry, in debates between the local and the global.